"Nervenaufpeitschende Aufklärung!": The Melodramatic Satire of John Heartfield's Photomontages. (2nd January 2017) - Kriebel, Sabine T.
Abstract : This essay investigates John Heartfield's invocation of the melodramatic mode in photomontages that he produced for the Communist mass-circulation journal Arbeiter Illustrierte Zeitung in the 1930s. In a reverse strategy of dehumanization, Heartfield loads the photomontages of his National Socialist foes with emotional surfeit — sensationalist pathos, copious weeping, and unhinged rage — in order to destabilize the gravitas of Nazi leadership. Illuminating the psychoanalytic and affective dimensions of Heartfield's project, the essay demonstrates the complex psychological and somatic operations involved in the manufacture of these seemingly simple, populist montages. Melodrama's aesthetics of overstatement charges the quotidian conflicts pictured in these photomontages with greater moral intensity or urgency, generating heightened psychological investment in the embodied reader during a fraught period in Europe's history.